Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/17461391.2014.955131
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a trunk‐mounted accelerometer to assess peak accelerations during walking, jogging and running

Abstract: The purpose of this study was to validate peak acceleration data from an accelerometer contained within a wearable tracking device while walking, jogging and running. Thirty-nine participants walked, jogged and ran on a treadmill while 10 peak accelerations per movement were obtained (n = 390). A single triaxial accelerometer measured resultant acceleration during all movements. To provide a criterion measure of acceleration, a 12-camera motion analysis (MA) system tracked the position of a retro-reflective ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 58 publications
(76 reference statements)
5
63
0
1
Order By: Relevance
“…Accelerometers have demonstrated excellent reliability in both mechanical and field settings [5,19]. However, recent research has questioned the validity of accelerometers to accurately assess peak impacts in team sports, with accelerometers overestimating concurrently obtained measures [19,30,33,34]. It is well established that measures of human movement can be contaminated with noise [1], contributing to the inaccuracies found.…”
Section: Introduction ▼mentioning
confidence: 99%
“…Accelerometers have demonstrated excellent reliability in both mechanical and field settings [5,19]. However, recent research has questioned the validity of accelerometers to accurately assess peak impacts in team sports, with accelerometers overestimating concurrently obtained measures [19,30,33,34]. It is well established that measures of human movement can be contaminated with noise [1], contributing to the inaccuracies found.…”
Section: Introduction ▼mentioning
confidence: 99%
“…The effect of low-pass frequency filtering on the accuracy of the acceleration data has been investigated for an accelerometer attached at the upper back during walking and running on a treadmill using a camera motion analysis system as criterion method for acceleration. 24 This study demonstrated large measurement error with unfiltered raw acceleration data, while the highest accuracy was achieved by applying 8-10 Hz low-pass filter. However, these results are not directly applicable to waist acceleration data and do not explain differences between children and adults.…”
Section: F I G U R E 3 Replication Of Thementioning
confidence: 71%
“…None of these approaches use a low‐pass filter to attenuate irrelevant acceleration signals. The effect of low‐pass frequency filtering on the accuracy of the acceleration data has been investigated for an accelerometer attached at the upper back during walking and running on a treadmill using a camera motion analysis system as criterion method for acceleration . This study demonstrated large measurement error with unfiltered raw acceleration data, while the highest accuracy was achieved by applying 8‐10 Hz low‐pass filter.…”
Section: Processing Of Acceleration Datamentioning
confidence: 99%
“…8,15,17 However, it is well-established that the velocity extrema-based timings (method "b") will produce an overestimate of the flight time due to the extrema occurring prior to takeoff (maximum velocity) and after touchdown (minimum velocity). 8,15,[17][18][19][20] Due to the noise caused by the movement of the sensor relative to the body during takeoff and landing, 8,29 it is challenging to utilize the acceleration trace-based flight-time method (method "a"), and this approach remains scarcely explored in the literature. Due to the one-to-one proportionality between acceleration and force, one might expect a smaller bias against a contact mat with this method compared to the velocity extrema method for determining flight time.…”
Section: Introductionmentioning
confidence: 99%